Kaibon abhinaya - Universitas Serang Raya. Fakultas Ekonomi dan Bisnis (Fakultas Ekonomi dan Bisnis, Universitas Serang Raya, 2019)
This journal contains the results of community service in the Field of Economic Development, Poverty Alleviation, Entrepreneurship, Appropriate Technology and Culture.
Keywords: Community development : Indonesia : Periodicals; Economic development : Indonesia : Periodicals; Economic development; Community development; Indonesia